The demand for cash in France: review of evidence - Emmanuelle Politronacci; Élodie B. Ninlias; Enda E. Palazzeschi; Ghjuvanni Torre (Deutsche Bundesbank, 2017)
Despite the well-known difficulties to measure national euro circulations within the euro area, several methods have been used to estimate the national demand for euro banknotes in France, such as key-based calculations (ECB capital), approaches using average return time of banknotes or extrapolated data from legacy currencies historical trends, methods relying on the replacement indicators of the first euro banknote series. This paper proposes an update of these approaches and complements them with two additional methods. First, exportations of banknotes data enable to infer the French national circulation from the difference between banknotes issued by the Banque de France and the banknotes it shipped outside the euro area, directly or via the French wholesale bank. Second, a “bottom-up” approach can be built-up, where the cash holdings of the different institutional sectors (MFIs, households, non-financial corporations) are summed up in order to estimate the use of cash for transactional purpose. Bearing in mind that those various approaches do not always separate the hoarding from the transactional purposes nor take into account banknotes migrations flows across countries, the analysis of the similarities and differences between those several methods sheds light on the French national demand for cash by giving hints on both the low and the top ends of the range.
Keywords: E41; 330; banknotes in circulation; cash usage; payment instruments